2015
DOI: 10.18223/hiscult.v4i1.1296
|View full text |Cite
|
Sign up to set email alerts
|

A SAGMACS no Brasil e o planejamento urbano em Belo Horizonte (1958-1962) * The SAGMACS in Brazil and the urban plan in Belo Horizonte (1958-1962)

Abstract: Resumo: O artigo enfoca a atuação da Sociedade de Análises Gráficas e Mecanográficas Aplicadas aos Complexos Sociais (SAGMACS) em Belo Horizonte. Analisa três aspectos da configuração social e política do planejamento urbano regional: a formação da SAGMACS e sua importância em projetos de modernização capitalista; a disputa da questão urbana (social) entre as diferentes culturas políticas; e o urbanismo na Escola de Arquitetura da Universidade de Minas Gerais. Palavras-chave: Urbanismo; Projetos de modernizaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to Silveira, Melo & Almeida (2002), there are ca. 192 species of indigenous stingless bees in Brazil, bred especially for honey production and its byproducts (Aquino, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Silveira, Melo & Almeida (2002), there are ca. 192 species of indigenous stingless bees in Brazil, bred especially for honey production and its byproducts (Aquino, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Conforme aponta Oliveira (2008) Art. 2º -Fica autorizada a abertura de um crédito especial no valor de CR$1650,00 para ocorrer às despesas a que se refere o artigo 1º (PORTEIRINHA, 1949, p. 381).…”
Section: Resultsunclassified
“…In contrast, there was no difference in the MFI of Bodipy 493/503 when comparing subpopulations of monocytes from the non-infected and IgM-negative groups. The gating strategy used to analyze the monocytes is demonstrated in Figure 2 B. DENV infection did not alter the MFI of Bodipy 493/503 in neutrophils, eosinophils, lymphocytes, NK and NK T cells [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the subpopulations of CD16 − and CD16 + monocytes of the IgM-negative group displayed higher levels of LBs compared with the non-infected group, whereas the other leucocytes presented levels of LBs similar to those of the uninfected group, independent of presence or absence of IgM [ 26 ]. In fact, Samsa et al (2009) [ 33 ] observed that BHK cells presented an increased number of LBs after in vitro infection by DENV-2.…”
Section: Discussionmentioning
confidence: 99%